INTRODUKSI TEKNOLOGI INOVASI AMBUL UNTUK BUDIDAYA TANAMAN SAYURAN DI KALIMANTAN TENGAH - HASTIN ERNAWATI NUR CHUSNUL CHOTIMAH; GUSTI IRYA ICHRIANI; ARDIANOR ARDIANOR (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2014)
Arut Bawah is a settlement that is always flooded every year due to Kahayan river run off . Residents perform various activities on the water, and transportation between housing residents with one another, using wooden boards. The conditions is not possible if it is used to grow crops. It is certainly limiting factor for household food needs, including the need for vegetables. Flooded land use around residential has not been done because the technology is not yet known. Through these activities, the community is expected to implement one of the local knowledges of the environment-friendly cultivation in swampy areas with ambul system so that people can still grow crops to sustain life. It consists of meeting nutritional needs, as well as improving food security in water-saturated soil conditions. This community service was conducted by the various stages of 1) outreach and dissemination of technology ambul 2) training of making ambul and 3) planting a variety of vegetables in ambul. The results showed that ambul can be used as a technology for cultivation in flooded areas. The introduction of technology ambul got a positive response from residents Arut Bawah Palangkaraya Central Kalimantan. Keywords: ambul, vegetables and flooded areas.